Fahaman Melampau Menurut Sheikh Ahmad Al-Fatani (M. 1908) Berdasarkan Kitab Hadiqatul Azhar War Rayahin : Extreme Thinking According To Sheikh Ahmad Al-Fatani (D. 1908) Based on The Book of Hadiqatul Azhar War Rayahin - Mohd Bakri, Mohamad Fikri; Mohd Nor, Mohd Roslan; Ibrahim, Muhammad Khalis (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2025)
Hadiqatul Azhar War Rayahin is a masterwork written at the end of the nineteenth century by Sheikh Ahmad al-Fatani that analyses the history of the Ottoman Empire, the stories of the scholars, and some discussions in many disciplines of knowledge. However, his work also documented the controversy over the radical ideas that existed at the time. This demonstrates the need of understanding the origins of this extreme thinking in order to avoid Muslims from being persuaded by it. The goal of this research is to identify the type of extreme belief and its characteristics that existed during the time of Sheikh Ahmad al-Fatani’s work, Hadiqatul Azhar War Rayahin. This study employs a qualitative research approach based on historical research and content analysis to examine the work of Sheikh Ahmad al-Fatani, Hadiqatul Azhar War Rayahin. The findings of this investigation demonstrate that Sheikh Ahmad al-Fatani has his own ideas on extremist beliefs that can endanger Muslims’ religious lives. This study contends that what Sheikh Ahmad al-Fatani described is critical for the current generation to utilise as a guideline to avoid religious extremism.